Parent‐ and self‐reported dimensions of oppositionality in youth: construct validity, concurrent validity, and the prediction of criminal outcomes in adulthood. (28th January 2013) - Aebi, Marcel; Plattner, Belinda; Metzke, Christa Winkler; Bessler, Cornelia; Steinhausen, Hans‐Christoph
<x xml:space="preserve">Abstract</x> Background: Different dimensions of oppositional defiant disorder (ODD) have been found as valid predictors of further mental health problems and antisocial behaviors in youth. The present study aimed at testing the construct, concurrent, and predictive validity of ODD dimensions derived from parent‐ and self‐report measures. Method: Confirmatory factor analyses were performed to test a three‐dimensional model (ODD‐irritability, ODD‐headstrong, and ODD‐hurtful) and a two‐dimensional model (ODD‐irritability, ODD‐headstrong/hurtful) based on items of the Child Behavior Checklist (CBCL) and the Youth Self Report (YSR) collected in a Swiss community study of 1, 031 adolescents (519 boys, 512 girls) aged between 10.7 and 17.9 (M = 13.85, SD = 1.63) years. Logistic regression analyses were applied to predict scores in the clinical range of concurrent CBCL/YSR‐anxiety/depression, CBCL/YSR‐attention problems, and CBCL/YSR‐delinquent behavior and depression as measured by the Center for Epidemiological Studies Depression Scale (CES‐D) as well as to predict the presence of adult criminal convictions. Results: CFA findings were in favor of a three‐dimensional model rather than a two‐dimensional model of ODD. The CBCL/YSR‐ODD‐irritability scale was related to concurrent self‐reported depression, but also to attention problems and delinquent behavior. CBCL/YSR‐ODD‐hurtful and less strongly also the combined YSR‐headstrong/hurtful scale predicted adult criminal outcomes. Conclusions: As proposed by the DSM‐5 workgroup, different ODD‐dimensions were confirmed by the present study. ODD‐irritability predicts psychiatric comorbidity and ODD‐hurtful symptoms should be specifically considered in youth at risk for criminal outcomes.